Ontological aspects of early Jewish anthropology : the malleable self and the presence of God - Putthoff, Tyson L. (The Brill Reference Library of Judaism, 2017)
In Ontological Aspects of Early Jewish Anthropology , Tyson L. Putthoff explores early Jewish beliefs about how the human self reacts ontologically in God's presence. Combining contemporary theory with sound exegesis, Putthoff demonstrates that early Jews widely considered the self to be intrinsically malleable, such that it mimics the ontological state of the space it inhabits. In divine space, they believed, the self therefore shares in the ontological state of God himself. The book is critical for students and scholars alike. In putting forth a new framework for conceptualising early Jewish anthropology, it challenges scholars to rethink not only what early Jews believed about the self but how we approach the subject in the first place.